Physiological arousal and performance in elite archers: A field study - Robazza, C.; Bortoli, L.; Nougier, V. (European Psychologist, 1998)
Assessed the performance and heart rate of 10 17-40 yr old top-level female archers. This study was designed to (1) analyze the impact of physiological arousal on performance, (2) investigate whether heart rate deceleration during shooting is affected by arousal modification, and (3) verify whether heart rate deceleration appears under conditions of occluded vision and mental rehearsal or while simulating execution. Treatments comprised optimal, delayed, blind, simulated, high-arousal, and low-arousal shooting conditions. Shooting scores, variable error, and total error, and heart rate were assessed. Results reveal that best and worst outcomes were associated with optimal and delayed conditions, respectively. Decreased performance was also found for high arousal. Analysis of heart rate yielded significant results: Heart rate deceleration during shooting, from draw to release, was associated with optimal, blind, and simulated conditions. Implications for practice in archery are derived from findings. It is concluded that performance outcomes and heart rate pattern can be assessed during training to determine optimal arousal and action timing. Heart rate deceleration can be used as a physiological marker of modifications induced by mental rehearsal and skill simulation.